2004
DOI: 10.2337/diacare.27.2.530
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Coronary Heart Disease in Type 1 Diabetic Patients in Europe

Abstract: OBJECTIVE -The goal of the study was to examine risk factors in the prediction of coronary heart disease (CHD) and differences in men and women in the EURODIAB Prospective Complications Study. RESEARCH DESIGN AND METHODS -Baseline risk factors and CHD at follow-upwere assessed in 2,329 type 1 diabetic patients without prior CHD. CHD was defined as physician-diagnosed myocardial infarction, angina pectoris, coronary artery bypass graft surgery, and/or Minnesota-coded ischemic electrocardiograms or fatal CHD.RES… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
152
2
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(175 citation statements)
references
References 45 publications
(35 reference statements)
12
152
2
9
Order By: Relevance
“…In addition, gender differences in the prevalence of atherosclerosis in type 1 diabetes could possibly be explained by the observed findings during puberty. Contrary to the healthy population, incidence rates and mortality of coronary heart disease (CHD) in women with type 1 diabetes are equal or even higher than in men (36,37). In type 1 diabetes, coronary artery calcification is greatly increased and the gender difference in calcification is lost (38).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, gender differences in the prevalence of atherosclerosis in type 1 diabetes could possibly be explained by the observed findings during puberty. Contrary to the healthy population, incidence rates and mortality of coronary heart disease (CHD) in women with type 1 diabetes are equal or even higher than in men (36,37). In type 1 diabetes, coronary artery calcification is greatly increased and the gender difference in calcification is lost (38).…”
Section: Discussionmentioning
confidence: 99%
“…In type 1 diabetes, coronary artery calcification is greatly increased and the gender difference in calcification is lost (38). The cardioprotective gender effect in healthy women is not present any longer in type 1 diabetes (36,37). The reasons for the greater impact of CHD in women with type 1 diabetes are not clear and little of this gender effect can be explained by known risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…HbA 1c (normal range 2.9-4.8%) was measured by an enzyme immunoassay using a monoclonal antibody raised against HbA 1c (Dako, Ely, UK). Plasma levels of triacylglycerol, and total and HDL-cholesterol concentrations were determined by standard enzymatic methods (Boehringer Mannheim, Burgess Hill, UK) using a Cobas-bio centrifugal analyser (Roche, Welwyn Garden City, UK) [15]. For HDL, samples with triacylglycerol concentrations >3.0 mmol/l were diluted with 0.15 mol/l sodium chloride solution before chemical precipitation.…”
Section: Methodsmentioning
confidence: 99%
“…For HDL, samples with triacylglycerol concentrations >3.0 mmol/l were diluted with 0.15 mol/l sodium chloride solution before chemical precipitation. LDL-cholesterol was calculated from Friedewald's formula if triacylglycerol was below 4.5 mmol/l [15]. Fifteen patients did not have their LDL-cholesterol calculated.…”
Section: Methodsmentioning
confidence: 99%
“…The Wisconsin Epidemiologic Study of Diabetic Retinopathy (WESDR) reported that, whereas the HbA 1 level was associated with mortality from any heart disease (not controlling for renal disease), there was no significant relationship with myocardial infarction or angina specifically [7]. A significant age-and durationadjusted relationship reported in men (but not women) in the EURODIAB study disappeared with further adjustment for other cardiovascular risk factors [8]. A 10 year followup of patients at the Hvidore hospital in Denmark also failed to show an independent effect of HbA 1c , though the authors suggested that this might have been due to the small number of events [9].…”
Section: Introductionmentioning
confidence: 99%